Technology Revolution in Learning: Building the Future of Education - Meisuri Meisuri; Patriandi Nuswantoro; Budi Mardikawati; Loso Judijanto (Journal of Social Science Utilizing Technology, 2023)
Background. This research explores the impact of the technological revolution on learning, with a focus on teacher and student perceptions. In this digital era, technology integration has become the main foundation in the educational process. Purpose. The research aims to analyse the extent to which technology is integrated in learning, evaluate teachers' perceptions of the role of technology, assess the influence of technology in increasing student motivation and participation, and identify the main barriers to adopting technology. Method. This research method uses a quantitative research survey model with 15 education students selected by purposive sample. The data collection process included an initial questionnaire, direct observation of the use of technology in learning, and in-depth interviews. Results. The results of the study revealed that the use of technology has become a daily habit for education students, indicating significant integration of technology in the learning experience. The majority of respondents believe that technology can increase student motivation and have positive beliefs regarding the potential to personalize learning according to student needs. Conclusion. The conclusions of this study highlight the need for ongoing support for the development of teachers' technology skills, expanded integration of technology in the curriculum, and empowerment of students through technology to increase motivation and learning experiences. By adopting a thoughtful approach to the technological revolution in education, inclusive learning experiences and greater opportunities for innovation can be created, equipping students to face a future that is dynamic and responsive to technological change.